THE ROLE OF ISLAMIC ECONOMIC INSTITUTIONS TO RECOVER REAL SECTOR OF SMEs During COVID-19 Pandemic - Trimulato Trimulato (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2021)
Islamic economics prioritizes the real sector including SMEs, and makes Islamic Economic institutions as supporters and drivers of the real sector. The market share of sharia financial has reached 8.5 percent, and will continue to grow and develop. Since the emergence of the corona virus outbreak, it has eroded and slowed down economic activity, including in the SMEs sector. SMEs are among the ones that have been significantly affected by the corona virus. To restore the economic activities of SMEs, the Islamic Economic Institutions have role to be able to restore the economic activities of SMEs. The purpose of this study is to determine the development of Islamic economic institutions, and to determine the role of Islamic economic institutions in restoring SMEs in the midst of the Covid-19 outbreak. This type of research is library research with qualitative characteristics. Sources of data in this research are secondary data sourced from several institutions that have been presented. The limitation in this study is only for a few Islamic economic institutions related to SMEs. The data analysis technique used in this research is descriptive qualitative. Describing the object of research on the development of Islamic economic institutions and the role of Islamic economic institutions to recover the real sector of SMEs is included in analysis technique. The results of this study indicate the development of Islamic economic institutions. Sharia Financing Banking (BPRS) grew by 349.34 for income, Sharia Microfinance Institutions (LKMS) grew by 11.75 percent for financing, Sharia Peer To Peer Landing (P2P) institutions experienced a decrease in assets by 0.05 percent, and Social institutions, the growth of social fund collection was 48.08 percent at Insisatif Zakat Indonesia (IZI), and the growth in distribution of social funds by 114.27 percent Badan Amil Zakat Nasional (BAZNAS). The role of Islamic economic institutions in the recovery of the real sector of SMEs in the midst of the Covid-19 outbreak, namely optimizing  finance for SMEs, assisting financing customers, providing relief for affected customers, participating in marketing customer products online, maximizing profit sharing system, strengthening of partnerships, and maximizing the distribution of social funds for SMEs economic activities.